Peningkatan Kualitas dan Diversifikasi Produk Ikan Teri untuk Pemberdayaan Masyarakat di Desa Saramaake, Halmahera Timur - Faleh Setia Budi; Dian Herawati; Joko Purnomo; Ujang Sehabudin; . Sulistiono; Thomas Nugroho (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
Saramaake Village is one of the villages in East Halmahera District known as anchovy (Stolephorus spp) catching area. In this area, production of the anchovy is high and various in size. A community empowerment had been done for 7 months, from June 2016–January 2017, aimed to improve the anchovy product quality and product diversification. Methods used in this activity were training and mentoring. Targets of the activity were fishermen (15 fisherman groups or 60 persons; for fish catch product handling), and fisherman’s wife (2 groups or 11 persons; for product diversification). The activities that had been carried out were product quality improvement (fish drying construction, fish storage room rehabilitation), added value improvement (product diversification), packaging and labelling of the product. Based on the observation, the community had gained a knowledge and technology related to the fish handling and processing. Some communities had applied the technology of manufacturing processed products, as well as doing the packaging and labeling of these products.